Peningkatan Proses Pembelajaran Tematik Terpadu Menggunakan Model Cooperative Learning Tipe CRH di Kelas V SD - Dora Madona; Farida S (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2021)
This Study aims to determine the effect of Course Review Horay (CRH) modeling method on integrated thematic learning process. This research is a classroom action research using qualitative and quantitative approaches. In the implementation, this research consists of two  cycles, namely cycle I two meetings and cycle II one meeting. Includes four stages, namely planning, implementation, observation and reflection. The subjects of this research were 30 studen in class V. The result of cycle research on RPP meeting one earn a percentage value of 69,44% (C) increasing 83,33% (B) in meeting two and increasing 97,22% (AB) in cycle two. At theacher of the cycle realese one earn a percentage value of 73,68% (B) increasing 81,57% (B) at meeting two and increasing 95,05% (AB) it cycle two. Whereas at the activities of student cycle one a percentage of 72,36% (B) increase 80,26 (B) at meeting two increase 94,73 (AB) in cycle two. Ths the Cooperative Learning model type Course Review  Horay has been able to improve student learning procces in Integrated Thematic learning in class V SDN 06 Padang Besi Kota Padang.